1989
DOI: 10.1126/science.2476847
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Bacterial Porin Gene Expression by a Chimeric Signal Transducer in Response to Aspartate

Abstract: The Tar chemoreceptor of Escherichia coli is a membrane-bound sensory protein that facilitates bacterial chemotaxis in response to aspartate. The EnvZ molecule has a membrane topology similar to Tar and is a putative osmosensor that is required for osmoregulation of the genes for the major outer membrane porin proteins, OmpF and OmpC. The cytoplasmic signaling domain of Tar was replaced with the carboxyl portion of EnvZ, and the resulting chimeric receptor activated transcription of the ompC gene in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
172
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 200 publications
(179 citation statements)
references
References 23 publications
2
172
2
Order By: Relevance
“…The phenotypes of different Tar-EnvZ hybrid receptors in the present paper (Tez5, -6, -7, -8, and -9) as well as those of Taz1 and Taz2-1 in the previous works (9,12) suggest that both the Tar linker and the EnvZ linker need to be intact for fulfilling their function, and specific interactions between helix I and helix II in the linker is important for signal transduction. Particularly, helix II may serve as an effector element within the linker for further signal propagation, as it may form a long coiled-coil structure together with helix I of domain A of EnvZ based on LEARNCOIL prediction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The phenotypes of different Tar-EnvZ hybrid receptors in the present paper (Tez5, -6, -7, -8, and -9) as well as those of Taz1 and Taz2-1 in the previous works (9,12) suggest that both the Tar linker and the EnvZ linker need to be intact for fulfilling their function, and specific interactions between helix I and helix II in the linker is important for signal transduction. Particularly, helix II may serve as an effector element within the linker for further signal propagation, as it may form a long coiled-coil structure together with helix I of domain A of EnvZ based on LEARNCOIL prediction.…”
Section: Discussionmentioning
confidence: 98%
“…The resultant Taz (12) and Trz (13) are able to respond to aspartate and ribose in the medium, respectively, to activate ompC-lacZ in a concentration-dependent manner, suggesting that the chemoreceptors and EnvZ share a common signal transduction mechanism. Similar chimeric receptors have also been constructed using the periplasmic and transmembrane domain of Tar and the cytoplasmic domain of the human insulin receptor (14) or the periplasmic domain of the histidine kinase NarX and the cytoplasmic domain of Tar (15), further supporting a notion that there is a common mechanism widely used by signal transduction across the membrane in both prokaryotes and eukaryotes.…”
mentioning
confidence: 99%
“…To gain insight into transmembrane signal transduction mechanisms of EnvZ, several groups have constructed aspartate-and ribose-responsive chimaeric proteins consisting of the N-terminal periplasmic and transmembrane domains of the Tar or Trg chemoreceptors respectively, and the cytoplasmic catalytic domain of EnvZ [11,12]. Studies on these chimaeric proteins [13,14], combined with mutagenesis analysis [15,16], have shown that the transmembrane, as well as the linker helices, plays a role in signal propagation.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Adapting the ability to rewire twocomponent pathways for synthetic biology efforts. Methods for rationally redirecting information flow within bacteria combined with advances in engineering histidine kinases with desired sensory capabilities [49][50][51] will enable the construction of sophisticated new signaling circuits.…”
Section: Discussionmentioning
confidence: 99%